2022
DOI: 10.1039/d2cp02061k
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the stability–performance contradiction of cage-like high-energy-density materials by a backbone-collapse and branch-heterolysis competition mechanism

Abstract: Searching for advanced strategies to alleviate the inherent contradiction between stability and performance has been one of the most challenging tasks in the development of high-energy-density materials (HEDMs) for centuries....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…For centuries, researchers have been faced with the daunting task of finding effective strategies to address the inherent trade‐off between stability and performance in the development of high‐energy‐density materials (HEDMs). Recently, Song et al [297] . demonstrated that caged HEDMs have the potential to show both high thermal stability and high performance using the ML‐accelerated HTC technique.…”
Section: Applications Of Htc In Materials Developmentmentioning
confidence: 99%
“…For centuries, researchers have been faced with the daunting task of finding effective strategies to address the inherent trade‐off between stability and performance in the development of high‐energy‐density materials (HEDMs). Recently, Song et al [297] . demonstrated that caged HEDMs have the potential to show both high thermal stability and high performance using the ML‐accelerated HTC technique.…”
Section: Applications Of Htc In Materials Developmentmentioning
confidence: 99%
“…With the development of computational level, theoretical chemistry and high-throughput screen inject new vitality into the search for energetic materials under the consideration of cost and safety. [13][14][15] During the high-throughput screen, machine learning offers a vital tool for effective performance prediction, such as density, [16][17][18] heat of formation, 19,20 detonation properties, [21][22][23] and decomposition temperature. [24][25][26][27] We have explored to some extent in this eld as well: in 2021, we conducted a domain-related knowledge-promoted highthroughput cage scaffold screening from the ZINC15 database containing over 130 000 scaffolds and merged it with a combinatorial design to alleviate the lack of cage energetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Since HEDMs have adjustable thermodynamic and kinetic stability, they can be utilized for various energetic applications in real life. [6] Most organic compounds with a maximum number of heteroatoms, such as nitrogen and oxygen, store abundant chemical energy that is released upon external shock. In general, energy-rich materials are unstable under normal environmental conditions, such as heat, friction, shock, etc., and these properties lead to the instability of the materials.…”
Section: Introductionmentioning
confidence: 99%